IDENTIFICATION OF THE SPREAD OF THE RG-32 SANDSTONE RESERVOIR USING A SEQUENCY STRATIGRAPHY APPROACH IN THE NORTH WEST JAVA BASIN - Rizqi Afimanya, Aldifa
The Upper Cibulakan Formation of the Offshore North West Java (ONWJ) block has a thickness of up to 500 m and contains bedded lithology of shale, sandstone, siltstone and limestone. RG-32 sandstone is part of the Upper Cibulakan Formation, which is one of the main reservoirs at PHE ONWJ with log characteristics in the form of upward roughness and is characterized by clastic sedimentary deposits in a shallow marine environment with the influence of strong tidal currents (shelf sand ridge). The RG-32 reservoir has a wide distribution covering several fields, including Fields B, K, U, and South E, but the RG-32 reservoir does not develop in Fields E Main, L, and KL. The purpose of this research is to determine the distribution trend and depositional geometry of RG-32 sandstones. Sequence stratigraphy method is used to divide the Upper Cibulakan Formation into several parasequences. Integration of core rock data, biostratigraphy, wire rope log data, and 3D seismic was used to obtain RG-32 sandstone parasequence correlations in geological time scale framework. RG-32 sandstone is a parasequence of a tidal shelf sand ridge growth cycle. These sandstones were deposited during the Transgressive System Tract which developed in the dominant eastern part of the study area and generally has a north-south lateral distribution trend. The geometry of the RG-32 sandstone ridge is up to 60 km long and up to 10 km wide.